2017
DOI: 10.1016/s2542-5196(17)30041-4
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and cognitive decline in the aftermath of a natural disaster: a natural experiment from the 2011 Great East Japan Earthquake and Tsunami

Abstract: Background We examined prospectively whether social capital mitigates the adverse effects of natural disaster on cognitive decline. Methods The baseline for our study was established seven months before the 2011 Great East Japan Earthquake and Tsunami in a survey of older community-dwelling adults who lived 80 kilometers west of the epicenter (59.0% response rate). Approximately two and a half years after the disaster, the follow-up survey gathered information about personal experiences of disaster as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 18 publications
(21 reference statements)
1
68
1
2
Order By: Relevance
“…We selected representative items of neighborhood‐based individual social capital based on the World Bank's social capital questionnaire for assessing relationships to the outer neighborhood. Cognitive social capital was measured by trust in neighbors and perceived neighborhood safety . The former variable was evaluated by asking trust in people in the neighborhood nearby.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We selected representative items of neighborhood‐based individual social capital based on the World Bank's social capital questionnaire for assessing relationships to the outer neighborhood. Cognitive social capital was measured by trust in neighbors and perceived neighborhood safety . The former variable was evaluated by asking trust in people in the neighborhood nearby.…”
Section: Methodsmentioning
confidence: 99%
“…The structural social capital plays a strong role in determining the social ties and social participation among older adults, which can influence cognitive function and psychological wellbeing . A rich body of research has found that structural aspects of neighborhood‐based social capital, such as community participation and social activity, are positively associated with cognitive function among older adults . These studies document that communities endowed with higher stocks of social capital are better equipped to preserve higher cognitive function among older adults.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…More recently, Hikichi et al (2017) took advantage of a unique natural experiment to capture the buffer effect of SC on threats to cognitive function. This research prospectively examined the association between changes in SC and cognitive function, before and after the 2011 great east Japan earthquake and tsunami.…”
Section: So Cial C Apital and Neurolog Ic Al Conditionsmentioning
confidence: 99%